SOIL INFILTRATION RESPONDS TO POST-HARVESTING PRESCRIBED BURNING OF ACACIA PLANTATION IN A HEADWATER MOUNTAIN - Xuan Dung, Bui; Thuy Quynh, Kieu (Journal of Forestry Science and Technology, 2021)
To determine the responses of soil infiltration characteristics to post-harvesting prescribed burning of Acacia plantation forest in a headwater mountain of Vietnam. The field experiment for infiltration measurement was established at different stages (including 5-year-old Acacia forest, after harvesting, after prescribed burning and planting new young forest) from August to October 2020. A number of affecting factors were determined, including vegetation characteristics and soil physical characteristics of Acacia plantation. The main findings included: (1) Total time for one process from harvesting to planting new forest was nearly 30 days. Both factors of vegetation and soil properties changed during four stages; (2) The infiltration rate of all locations in all stages followed the trend of decreasing after harvesting, burning, and recovering after planting new forest. The infiltration accumulation, initial rate, and stable rate was highest in 5-year-old Acacia plantation (525.8 mm, 20.2 mm/min and 2.9 mm/min, respectively), and then decreased continuously to lowest position after burning (211.1 mm, 10.1 mm/min, 1.2 mm/min, respectively) and recovered when new forest was planted. The factors affect to soil initial infiltration were understory cover, dry bulk density and porosity. Besides, the factors influence stable rate were understory cover, canopy cover, dry bulk density, percentage of silt and clay in soil; (3) These findings suggest that improving soil quality and temporal infiltration rate are necessary during-after forest harvesting and soil treatment periods of Acacia plantation in headwater mountainous areas.